Spray deposited Hausmannite Mn3O4 thin films using aqueous/organic solvent mixture for supercapacitor applications. (10th July 2016) - Yadav, Abhijit A.; Jadhav, S.N.; Chougule, D.M.; Patil, P.D.; Chavan, U.J.; Kolekar, Y.D.
Graphical abstract: Highlights: Electrochemical properties of Mn3 O4 thin films. Crystallite size in the range of 14–19 nm. Highest specific capacitance of 394 F g −1 for film deposited at 350 °C. Specific energy and specific power are 8.27 Wh kg −1 and 850 W kg −1, respectively. Abstract: Manganese oxide (Mn3 O4 ) is considered one of the most promising materials for high-performance supercapacitors due to its extraordinary theoretical specific capacitance, low-cost, environmental benignity and natural abundance. Mn3 O4 thin films have been deposited by spray pyrolysis using aqueous/organic solvent mixture. These films were characterized for structural, morphological, optical and electrical measurements. The electrochemical performance of the supercapacitor was studied by using cyclic voltammetry curves recorded at different scan rates. The porous Mn3 O4 thin film electrode exhibits significantly improved supercapacitive performance in 1 M Na2 SO4 electrolyte with highest specific capacitance of 394 F g −1 at scan rate of 10 m Vs −1 for film deposited at 350 °C. The specific energy and specific power are found to be 8.27 Wh kg −1 and 850 W kg −1, respectively, at a current density of 1 A g −1 . The specific capacitance of the Mn3 O4 electrode maintains 93.01% of its initial value after 1000 cycles, at a current density of 1 A g −1 showing a good cycling stability.